The effect of temperature on the development of Nephus includens (Kirsch) and Nephus bisignatus (Boheman) (Coleoptera: Coccinellidae), predators of Planococcus citri Risso (Hemiptera: Pseudococcidae) - Kontodimas, D. C.; Lykouressis, D.; Karandinos, M. G.; Katsouannos, P.; Stathas, G. J.; Eliopoulos, P. A.; Economou, L. P. (ENTOMOLOGIA HELLENICA, 2004)
The effect of temperature οη the development of the predators Nephus includens (Kirsch) and Ν. bisignatus (Boheman) (Coleoptera: Coccinellidae), was studied. The development time of immature stages and the pre-oviposition period of adult females for the two predators was recorded at eight constant temperatures (10, 15, 20, 25, 30, 32.5, 35 and 37.5°C). The beetles were reared on eggs, nymphs and female adults of Planococcus citri (Risso) (Homoptera: Pseudococcidae) that had developed on squash (Cucurbita pepo) and on sour orange leaves (CΊtrus aurantium). Using the linear model for the biological cycle of Ν. includens on squash and on sour orange leaves, the developmental zeros (lower temperature thresholds) were estimated to be 10.9 and 11.0°C respectively and the thermal constants, 490.5 and 472.8 day-degrees respectively. Using the Lactin model the lower thresholds were estimated to be 11.1 and 11.2°C respectively and the upper thresholds 36.1 and 36.0°C respectively. For the biological cycle of Ν. bisignatus, using the linear model, the lower thresholds were estimated to be 9.4°C on squash and 9.3°C on sour orange leaves and the thermal constants were 614.3 and 647.9 day-degrees respectively. Using the Lactin model the lower thresholds were estimated to be 9.9 and 1O.0°C respectively and the upper thresholds, 34.7 and 35.0°C respectively. The survival rate of Ν. includens instars at 10, 15, 20, 25, 30, 32.5, 35 and 37.5°C on squash and on sour orange leaves was respectively 0.0, 34.9, 63.2, 70.6, 63.3, 54.5, 19.8, 0.0, and 0.0, 32.2, 61.0, 68.0, 68.3, 56.6, 17.6, 0.0%. The survival rate of Ν. bisignatus instars at 10, 15, 20, 25, 30, 32.5 and 35°C on squash and on sour orange leaves was respectively, 0.0, 39.9, 61.1, 60.7, 47.2, 26.4, 0.0 and 0.0, 35.7, 65.7, 68.0, 44.2, 29.1, 0.0%. The results show that Ν. includens has a shorter biological cycle than Ν. bisignatus, whereas the latter species has lower temperature thresholds.